Wnt10b and Dkk-1 gene therapy differentially influenced trabecular bone architecture, soft tissue integrity, and osteophytosis in a skeletally mature rat model of osteoarthritis. (2nd November 2017) - Mason, Jeffrey B.; Gurda, Brittney L.; Hankenson, Kurt D.; Harper, Lindsey R.; Carlson, Cathy S.; Wilson, James M.; Richardson, Dean W.
ABSTRACT: Aims: Our goals in the current experiments were to determine if (a) upregulation of Wnt signaling would induce osteoarthritis changes in stable stifle joints and (b) if downregulation of Wnt signaling in destabilized joints would influence the progression of OA. Methods: At 37 weeks of age, rats were injected in the stifle joint with a recombinant adeno-associated viral vector containing the Wnt-inhibitor Dkk-1 or a Wnt10b transgene. At 40 weeks of age, rats underwent surgical destabilization of the joint. At 50 weeks of age, stifle joints were submitted for micro-computed tomography and histopathological analysis. Results: Injection of either Wnt10b or Dkk-1 transgenes in stable joints improved bone architectural parameters, but worsened soft tissue integrity. Osteophytosis was decreased by Dkk-1, but unchanged by Wnt10b. Destabilization negatively influenced bone architecture, increased osteophytosis, and decreased soft tissue integrity. Dkk-1 exacerbated the negative effects of destabilization, whereas Wnt10b had little effect on these parameters. Osteophytosis was improved, whereas soft tissue integrity was worsened by both transgenes in destabilized joints. Conclusions : The Wnt-inhibitor Dkk-1 does not appear to completely inhibit the effects of Wnt signaling on bone remodeling. In vivo upregulation of Wnt10b and its inhibitor, Dkk-1, can produce both parallel or contrasting phenotypic responses depending on the specific parameter measured and the fidelity of the examined joint. These observations elucidate different roles for Wnt signaling in stable versus destabilized joints and may help to explain the conflicting results previously reported for the role of Dkk-1 in joint disease.